2008
DOI: 10.1111/j.1365-2427.2008.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding rates, assimilation efficiencies and growth of two amphipod species on biodeposited material from zebra mussels

Abstract: SUMMARY1. Accumulation of organic material by the zebra mussel Dreissena polymorpha is assumed to be the source of a biodeposition-based food web. However, only little is known about the importance of the biodeposited material as a food source and its contribution to increased abundances of macroinvertebrates in the presence of D. polymorpha. 2. Feeding, assimilation and growth of the amphipods Gammarus roeselii and Dikerogammarus villosus on food sources directly and indirectly associated with D. polymorpha (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 44 publications
3
61
0
Order By: Relevance
“…Differences in feeding rate between sexes should be considered more strongly in future experiments. Another difference between our study and that of Gergs & Rothhaupt (2008) is that we used living chironomid larvae while the latter authors used dead (commercially available frozen) larvae. Possibly usage of dead larvae compared to usage of living larvae may have an effect on consumption rate of both gammarids.…”
Section: Discussionmentioning
confidence: 95%
“…Differences in feeding rate between sexes should be considered more strongly in future experiments. Another difference between our study and that of Gergs & Rothhaupt (2008) is that we used living chironomid larvae while the latter authors used dead (commercially available frozen) larvae. Possibly usage of dead larvae compared to usage of living larvae may have an effect on consumption rate of both gammarids.…”
Section: Discussionmentioning
confidence: 95%
“…Notwithstanding these discrepancies, it can perceive the presence of a fish not only as a danger, but also as information about potential food resources (Paterson et al, 2013), especially if the fish consumed chironomids-an important part of the diet of invasive amphipods (Bacela-Spychalska & van der Velde, 2013). Amphipods were found to assimilate and grow better on chironomids than on plant food (Gergs & Rothhaupt, 2008), thus chironomids seems likely to be their preferred food type. In such a situation, amphipods attracted to fish may benefit from feeding directly on fish faeces or from finding an area rich in their prey.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of mussels upon gammarids was observed in several studies. Chaetogammarus ischnus and Gammarus fasciatus Say, 1818 survived better in mussel colonies when exposed to fish predation (Gonzalez & Burkart 2004) and D. villosus grew faster on mussel pseudofaeces than on plant material (Gergs & Rothhaupt 2008a).…”
Section: Responses Of Macroinvertebrates To Mussel Bedsmentioning
confidence: 98%
“…Furthermore, another Ponto-Caspian species, D. villosus, was observed in high numbers among zebra mussel shells in the field (Devin et al, 2003;Boets et al, 2010) and showed active preferences for shells and living specimens of another invasive bivalve, Corbicula fluminea (O. F. Müller, 1774), in the laboratory (Werner & Rothhaupt, 2008). Gammarids can benefit from the presence of zebra mussels by using their shells as shelters as well as utilizing food resources provided by bivalves, such as increased abundance of benthic prey, faeces and pseudofaeces (Gonzalez & Burkart, 2004;Gergs & Rothhaupt, 2008a). Moreover, gammarids living among mussel shells were found to affect their molluscan hosts by modifying their attachment to substratum and locomotion (Kobak et al, 2012) as well as biting their fresh byssal threads (Platvoet et al, 2009.…”
Section: Introductionmentioning
confidence: 99%